LBA1 Clinical efficacy of atezolizumab (atezo) in biomarker subgroups by SP142, SP263 and 22C3 PD-L1 immunohistochemistry (IHC) assays and by blood tumour mutational burden (bTMB): Results from the IMpower110 study. (15th December 2019) - Herbst, R S; de Marinis, F; Giaccone, G; Reinmuth, N; Vergnenegre, A; Barrios, C H; Morise, M; Felip, E; Andric, Z; Geater, S; Ozguroglu, M; Mocci, S; et al.
Abstract: Background: The phase III IMpower110 study (NCT02409342) is evaluating atezo (anti–PD-L1) monotherapy as 1L treatment (tx) in PD-L1–selected patients (pts) with NSCLC independent of tumour histology. IMpower110 met its primary endpoint with significant OS improvement in PD-L1–high (TC3 or IC3; ≥ 50% tumour cell [TC] or ≥ 10% tumour-infiltrating immune cell [IC]; VENTANA SP142 IHC assay) wild-type (WT; EGFR/ALK-negative) pts (HR, 0.59 [95% CI: 0.40, 0.89]; P = 0.0106). Efficacy analyses in prespecified biomarker subgroups by the SP263 and 22C3 PD-L1 IHC assays and bTMB are reported. Methods: IMpower110 enrolled 572 chemo-naive pts with stage IV NSCLC, PD-L1 ≥ 1% TC or IC (TC1/2/3 or IC1/2/3; SP142), measurable disease by RECIST 1.1 and ECOG PS 0-1. Pts were randomised 1:1 to receive atezo 1200 mg IV q3w or platinum-based chemo (4 or 6 21-day cycles). OS (primary endpoint) was tested hierarchically in WT pts. Additional analyses included OS and PFS in the SP263 and 22C3 PD-L1 IHC and bTMB populations. PD-L1 cutoffs of ≥ 1% and ≥ 50% tumour proportion score (TPS) for 22C3 and ≥ 1% and ≥ 50% TC for SP263 were evaluated; bTMB cutoffs were ≥10, ≥ 16 and ≥ 20. Results: Biomarker-evaluable populations (BEP) in the TC1/2/3 or IC1/2/3 WT population (SP142; 554) included 534 (22C3), 546 (SP263) and 389 (bTMB) pts. Baseline characteristics in the IHC and bTMB BEP subgroups were generally balanced. OS and PFS in the PD-L1–high (TC3 or IC3; ≥ 50% TPS; ≥ 50% TC) subgroups favoured atezo (OS data shown in the table). Stepwise OS and PFS improvement, favouring atezo, was seen up to bTMB ≥ 16; no further benefit was seen at ≥ 20. Conclusion: Pt subgroups defined as PD-L1–high by all 3 IHC assays (SP142, 22C3, SP263) had similar OS and PFS benefit with atezo, despite the different assay sensitivities and scoring algorithms. Enrichment in clinical benefit, favouring atezo, was also seen in bTMB positive subgroups. Atezo monotherapy is a potential new 1L tx option for pts with PD-L1–high NSCLC. Clinical trial identification: NCT02409342. Editorial acknowledgement: Medical writing assistance for this abstract was provided by Kia C. E. Walcott, PhD, of Health Interactions, and funded by F. Hoffmann-La Roche, Ltd. Legal entity responsible for the study: F. Hoffmann-La Roche. Funding: F. Hoffmann-La Roche. Disclosure: R.S. Herbst: Advisory / Consultancy: Abbvie Pharmaceuticals; Advisory / Consultancy: ARMO Biosciences; Advisory / Consultancy, Research grant / Funding (institution): AstraZeneca; Advisory / Consultancy: Biodesix; Advisory / Consultancy: Bristol‐Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution): Eli Lilly and Company; Advisory / Consultancy: EMD Serrano; Advisory / Consultancy: Genentech/Roche; Advisory / Consultancy: Genmab; Advisory / Consultancy: Heat Biologics; Advisory / Consultancy: Halozyme; Advisory / Consultancy: Loxo Oncology; Advisory / Consultancy, Research grant / Funding (institution): Merck and Company; Advisory / Consultancy: Novartis; Advisory / Consultancy: Pfizer, Sanofi, Seattle Genetics, Nektar; Advisory / Consultancy: Shire PLC, Spectrum Pharmaceuticals, Symphogen, Tocagen, Tesaro ; Advisory / Consultancy: Neon Therapeutics; Advisory / Consultancy: Infinity Pharmaceuticals; Advisory / Consultancy: NextCure; Advisory / Consultancy: Junshi Pharmaceuticals. F. de Marinis: Research grant / Funding (self): F. Hoffmann-La Roche. G. Giaccone: Research grant / Funding (self): F. Hoffmann-La Roche. N. Reinmuth: Research grant / Funding (self): F. Hoffmann-La Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: AstraZeneca; Advisory / Consultancy, Speaker Bureau / Expert testimony: Bristol-Myers Squibb; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer-Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony: Lilly; Advisory / Consultancy, Speaker Bureau / Expert testimony: MSD; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Takeda. A. Vergnenegre: Advisory / Consultancy, Research grant / Funding (self), Travel / Accommodation / Expenses: F. Hoffmann-La Roche. C.H. Barrios: Research grant / Funding (self): Abbvie; Research grant / Funding (self): Amgen; Research grant / Funding (self): Astellas Pharma; Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Research grant / Funding (self): Bristol-Myers Squibb; Research grant / Funding (self): Celgene; Research grant / Funding (self): Covance; Research grant / Funding (self): Lilly; Research grant / Funding (self): Medivation; Research grant / Funding (self): Merck Serono; Advisory / Consultancy, Research grant / Funding (self): Merck Sharp Dohme (MSD) ; Advisory / Consultancy, Research grant / Funding (self): Novartis; Advisory / Consultancy, Research grant / Funding (self): Pfizer; Research grant / Funding (self): PharmaMar; Advisory / Consultancy, Research grant / Funding (self): Roche/Genentech; Research grant / Funding (self): CPO; Research grant / Funding (self): PUCRS; Research grant / Funding (self): LACOG; Research grant / Funding (self): GBECAM; Research grant / Funding (self): INCA-Brazil; Advisory / Consultancy: Boehringer-Ingelheim; Advisory / Consultancy: GSK; Advisory / Consultancy: EIsai; Advisory / Consultancy: Bayer. M. Morise: Research grant / Funding (self): F. Hoffmann-La Roche; Honoraria (self), Lecture fee: Eli Lilly; Honoraria (self), Research grant / Funding (self), Lecture fee, Principal investigator of contact clinical trial: Chugai; Honoraria (self), Research grant / Funding (self), Lecture fee. Principal investigator of contact clinical trial: Astra Zeneca; Honoraria (self), Lecture fee: Ono; Honoraria (self), Research grant / Funding (self), Lecture fee, Principal investigator of contact clinical trial: Pfizer; Honoraria (self), Lecture fee: MSD; Research grant / Funding (self), Principal investigator of contact clinical trial: Merk serono; Research grant / Funding (self), Principal investigator of contact clinical trial: Kissei; Research grant / Funding (self), Principal investigator of contact clinical trial: Taiho; Research grant / Funding (self), Principal investigator of contact clinical trial: Novartis; Research grant / Funding (self): Boehringer-ingelheim. E. Felip: Research grant / Funding (self): F. Hoffmann-La Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony: Abbvie; Advisory / Consultancy, Speaker Bureau / Expert testimony: Astra Zeneca; Advisory / Consultancy: Bergenbio; Advisory / Consultancy: Blue Print Medicine; Advisory / Consultancy, Speaker Bureau / Expert testimony: Boehringer Ingelheim; Advisory / Consultancy, Speaker Bureau / Expert testimony: BMS; Advisory / Consultancy: Celgene; Advisory / Consultancy, Speaker Bureau / Expert testimony: Eli Lilly; Advisory / Consultancy: Guardant Health; Advisory / Consultancy: Janssen; Advisory / Consultancy, Speaker Bureau / Expert testimony: Medscape; Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck KgaA; Advisory / Consultancy, Speaker Bureau / Expert testimony: Merck Sharp & Dohme; Advisory / Consultancy, Speaker Bureau / Expert testimony: Novartis; Advisory / Consultancy, Speaker Bureau / Expert testimony: Pfizer; Advisory / Consultancy: Prime Oncology; Advisory / Consultancy, Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy: Samsung; Advisory / Consultancy, Speaker Bureau / Expert testimony: Takeda; Advisory / Consultancy: Touchtime. Z. Andric: Research grant / Funding (self): F. Hoffmann-La Roche. S. Geater: Research grant / Funding (self): F. Hoffmann-La Roche. M. Ozguroglu: Research grant / Funding (self): F. Hoffmann-La Roche.S. Mocci: Full / Part-time employment: Genentech, Inc. M. McCleland: Full / Part-time employment: Genentech, Inc.. W. Zou: Full / Part-time employment: Genentech, Inc.. I. Enquist: Full / Part-time employment: Genentech, Inc.. K. Komatsubara: Full / Part-time employment: Genentech, Inc.. Y. Deng: Full / Part-time employment: Genentech, Inc.. H. Kuriki: Full / Part-time employment: Genentech, Inc.. D.R. Spigel: Research grant / Funding (institution): F. Hoffmann-La Roche; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Genetech/Roche; Advisory / Consultancy, Research grant / Funding (institution): Novartis; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Celgene; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Bristol-Myers Squibb; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: AstraZeneca; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy, Research grant / Funding (institution), Travel / Accommodation / Expenses: Boehringer Ingelheim; Advisory / Consultancy, Research grant / Funding (institution): Abbvie; Advisory / Consultancy, Research grant / Funding (institution): Foundation Medicine; Advisory / Consultancy, Research grant / Funding (institution): GlaxoSmithKline; Advisory / Consultancy, Research grant / Funding (institution): Lilly; Advisory / Consultancy, Research grant / Funding (institution): Merck; Advisory / Consultancy: Moderna Therapeutics; Advisory / Consultancy, Research grant / Funding (institution): Nektar; Advisory / Consultancy, Research grant / Funding (institution): Takeda; Advisory / Consultancy, Research grant / Funding (institution): Amgen; Advisory / Consultancy: TRM Oncology; Advisory / Consultancy: Precision Oncology; Advisory / Consultancy: Evelo Therapeutics; Advisory / Consultancy: Illumina; Advisory / Consultancy: PharmaMar; Research grant / Funding (institution): University of Texas Southwestern Medical Center- Simmons Cancer Center; Research grant / Funding (institution): G1 Therapeutics; Research grant / Funding (institution): Neon Therapeutics; Research grant / Funding (institution): Celldex; Research grant / Funding (institution): Clovis Oncology; Research grant / Funding (institution): Daiichi Sankyo; Research grant / Funding (institution), Travel / Accommodation / Expenses: EMD Serono; Research grant / Funding (institution): Acerta Pharma; Research grant / Funding (institution): Oncogenex; Research grant / Funding (institution): Astellas Pharma; Research grant / Funding (institution): GRAIL; Research grant / Funding (institution): Transgene; Research grant / Funding (institution): Aeglea Biotherapeutics; Research grant / Funding (institution): Tesaro; Research grant / Funding (institution): Ipsen; Research grant / Funding (institution): ARMO BioSciences; Research grant / Funding (institution): Millennium; Travel / Accommodation / Expenses: Genzyme; Travel / Accommodation / Expenses: Intuitive Surgical; Travel / Accommodation / Expenses: Purdue Pharma; Travel / Accommodation / Expenses: Spectrum Pharmaceuticals; Travel / Accommodation / Expenses: Sysmex. J. Jassem: Research grant / Funding (self): F. Hoffmann-La Roche; Speaker Bureau / Expert testimony: Roche; Advisory / Consultancy, Speaker Bureau / Expert testimony, Travel / Accommodation / Expenses: Pfizer; Advisory / Consultancy, Speaker Bureau / Expert testimony: Astra Zeneca; Advisory / Consultancy: BMS; Advisory / Consultancy: MSD; Advisory / Consultancy: Takeda; Travel / Accommodation / Expenses: Roche.